2022
DOI: 10.1107/s2052520622010393
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure of high-purity BaCe0.25Mn0.75O3: an improved material for thermochemical water splitting

Abstract: Solar thermochemical hydrogen production (STCH) via redox-active metal oxides is an approach for direct solar-driven hydrogen generation typically using a high-temperature redox cycle involving refractory oxides and steam. Typical cycles involve high-temperature reduction of oxides to form oxygen vacancies, followed by lower temperature reaction between oxygen vacancies and steam where the oxide is re-oxidized and the steam is reduced to hydrogen. Only a few materials have demonstrated reversible cycling under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…A summary of the weight fractions of each phase identified via Rietveld refinement is presented in Table S2, confirming the high phase purity of 12R-BCM and 12R-BPM. This sample of 12R-BCM has a phase purity of 98.39 ± 0.1 wt %, consistent with previous reports using the same synthesis . Very small (<1 wt %) amounts of impurity phases Ba 4 Mn 3 O 10 , BaCeO 3 , and CeO 2 were identified via Rietveld refinement.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…A summary of the weight fractions of each phase identified via Rietveld refinement is presented in Table S2, confirming the high phase purity of 12R-BCM and 12R-BPM. This sample of 12R-BCM has a phase purity of 98.39 ± 0.1 wt %, consistent with previous reports using the same synthesis . Very small (<1 wt %) amounts of impurity phases Ba 4 Mn 3 O 10 , BaCeO 3 , and CeO 2 were identified via Rietveld refinement.…”
Section: Resultssupporting
confidence: 89%
“…Comparing the low- and room-temperature PXRD data (Figures and S1) indicates that for both materials, no structural differences or symmetry lowering are present between 100 and 300 K, beyond anisotropic thermal expansion similar to that observed at elevated temperatures for 12R-BCM . Lattice parameters and refinement details are listed in Table S1.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…In situ XRD measurements (e.g., high temperature and controlled gaseous environments) provide a valuable route for deriving relationships between atmospheric redox conditions and material structure (i.e., structure-property relationships) (Metcalfe et al, 2019;Mastronardo et al, 2020). The advantage of XRD with a synchrotron source is exemplified by Bell et al (2022), where impurity phases at less than 0.4 weight percent were identified within the high-purity STCH material BCM, as well as by Strange et al (2022), where a novel BCM polytype was identified and found to form under high-temperature reducing conditions. The results described in both studies would have not been observed with conventional laboratory-source XRD.…”
Section: Application Of X-ray Diffraction To Solar Thermochemical Hyd...mentioning
confidence: 99%